2001
DOI: 10.1007/s005860000231
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI of the spine: different patterns of positions of the forward flexed lumbar spine in healthy subjects

Abstract: IntroductionImaging of the flexed and extended spine has been carried out since the first half of the 20th century using lateral radiographs [3,8]. With this technique, the examined subject is exposed to ionizing radiation with no assessment of soft tissues or axial plane imaging. Magnetic resonance imaging (MRI) provides excellent anatomical details in all planes without exposure to ionizing radiation. In the past, restrictions existed for functional lumbar spinal imaging, because of the systems' configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The use of kMRI may be helpful in these situations in determining spinal stability. [25][26][27][28][29] Combined with digital imaging software that allows for accurate and precise quantifi cation of spinal motion, kMRIs could potentially help spine surgeons create more complete clinical assessments of their patients in some situations. 30 , 31 Previous reports have shown that disc degeneration is strongly associated with changes in segmental motion.…”
Section: Discussionmentioning
confidence: 99%
“…The use of kMRI may be helpful in these situations in determining spinal stability. [25][26][27][28][29] Combined with digital imaging software that allows for accurate and precise quantifi cation of spinal motion, kMRIs could potentially help spine surgeons create more complete clinical assessments of their patients in some situations. 30 , 31 Previous reports have shown that disc degeneration is strongly associated with changes in segmental motion.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,13,17 Asymmetry of craniocervical joints occurred in 58% at the occiput-C1 levels and in 46% at the C1-2 levels in a study by Pfirrmann and colleagues. 12 This is often noted in daily clinical practice while analyzing computerized tomography or magnetic resonance images of the spine.…”
Section: Degenerative Changes In the Ccjmentioning
confidence: 94%
“…A modification of White and Panjabi's method was used with the Cobb angle measurement tool (Centricity Enterprise Web V3.0 software, GE Healthcare, Little Chalfont, United Kingdom) to measure the ROM angles. [16][17][18] Angle values in kyphosis, as usually observed in flexion (►Fig. 1A, C), were recorded as positive values, and angle values in lordosis, as usually observed in extension, were recorded as negative values (►Fig.…”
Section: Methodsmentioning
confidence: 99%